(untitled) (African Human Mobility Review, 2021)
In recent years, there has been increased migration of pastoralists from countries in Central and West Africa into Nigeria. Such movements are supported by the ECOWAS Transhumance Protocol and the Nigerian Constitution respectively. The movement of pastoralists has been associated with multi-dimensional practical and policy implications. This paper reflects on the policy implications of the migration of pastoralists across and within the borders of Nigeria and presents pointers to the areas for future policy intervention and research. The paper relied on existing policies like the ECOWAS Transhumance Protocol, the Nigerian Constitution and the Open Grazing Prohibition Law enacted by the Benue State government to draw inferences about the relevance and effectiveness of such laws in Nigeria. Interviews with farmers and pastoralists were conducted in 2017 to augment the policy analysis. The paper reports that the provisions of the ECOWAS Transhumance Protocol, like the possession of the International Transhumance Certificate as a mandatory entry requirement, have not been implemented in Nigeria.